Maternal and Cord Blood Vitamin D Status and Anthropometric Measurements in Term Newborns at Birth - Wierzejska, Regina; Jarosz, Mirosław; Klemińska-Nowak, Magdalena; Tomaszewska, Marta; Sawicki, Włodzimierz; Bachanek, Michał; Siuba-Strzelińska, Magdalena (Frontiers in Endocrinology, 2018)
Introduction: Vitamin D deficiency in pregnant women may result in reduced neonatal development due to the fact that systemic vitamin D status during fetal life depends on maternal concentrations. Some authors reported significant differences in neonatal anthropometric measurements depending on maternal vitamin D concentrations. Objective: Evaluation of the relationship between maternal and cord blood concentrations of vitamin D and neonatal anthropometric measurements at birth. Material and methods: The study included 94 pregnant women, at term, who delivered at the Department of Obstetrics, Women’s Diseases and Gynecological Oncology, Medical University of Warsaw. Total serum 25(OH)D concentration was measured in mother-child pairs and newborn anthropometric data were collected. A multiple regression analysis was used for statistical analysis. Results: No relationship between maternal and neonatal cord blood vitamin D concentrations versus neonatal weight, length, head and chest circumference at birth was found (p>0.05). Severe vitamin D deficiency (<10 ng/ml) was detected in 10.6%, deficiency (10-20 ng/ml) in 39.4%, insufficiency (20-30 ng/ml) in 39.4%, and optimal vitamin D concentration (>30 ng/ml) only in 10.6% of the pregnant women. Cord blood vitamin D deficiency (<20 ng/ml) was found in 28.7% of the neonates. Conclusions: No differences between neonatal anthropometric measurements of infants born to mothers with normal and deficient vitamin D concentrations were found.